EXPLORING THE EXPERIENCES OF TEACHERS AND STUDENTS IN IMPLEMENTING FINANCIAL LITERACY IN SCHOOLS: A GROUNDED THEORY APPROACH - Ristantri, Citra Dwi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to explore the experiences of teachers and students in implementing financial literacy programs in schools. By adopting a grounded theory approach, the study seeks to understand the challenges and opportunities encountered, as well as the factors that influence the effectiveness of these programs. Method: This study employed a qualitative research approach, specifically grounded theory methodology, to explore the experiences of teachers and students in implementing financial literacy programs in schools. Grounded theory is an inductive approach that allows for the development of theory from data collected systematically and analyzed through an iterative process. Results: The study found that teacher training, student engagement, and institutional support are key to successful financial literacy programs. Challenges include limited resources and curriculum constraints, while practical, real-life applications enhance student interest. Effective implementation requires a balanced approach addressing both obstacles and opportunities. Novelty: Novelty refers to the unique and original aspects of your research. It highlights what makes your study stand out from previous work in the field.